Black radical : the life and times of William Monroe Trotter - Greenidge, Kerri (2020)
"This long-overdue biography reestablishes William Monroe Trotter's essential place next to Douglass, Du Bois, and King in the pantheon of American civil rights heroes. William Monroe Trotter (1872- 1934), though still virtually unknown to the wider public, was an unlikely American hero. With the stylistic verve of a newspaperman and the unwavering fearlessness of an emancipator, he galvanized black working- class citizens to wield their political power despite the violent racism of post- Reconstruction America. For more than thirty years, the Harvard-educated Trotter edited and published the Guardian, a weekly Boston newspaper that was read across the nation. Defining himself against the gradualist politics of Booker T. Washington and the elitism of W. E. B. Du Bois, Trotter advocated for a radical vision of black liberation that prefigured leaders such as Marcus Garvey, Malcolm X, and Martin Luther King Jr. Synthesizing years of archival research, historian Kerri Greenidge renders the drama of turn- of- the- century America and reclaims Trotter as a seminal figure, whose prophetic, yet ultimately tragic, life offers a link between the vision of Frederick Douglass and black radicalism in the modern era"--
Introduction: Looking out from the dark tower -- Abolition's legacy : radical racial uplift and political independence -- Becoming the guardian : perils of conservative racial uplift -- The greatest race paper in the nation -- Of riots, suffrage leagues and the Niagara Movement -- Negrowump revival -- The new Negro legacy of the Trotter-Wilson conflict -- From Birth of a Nation to the National Race Congress -- Liberty's Congress -- The stormy petrel of the times -- Old Mon
Includes bibliographical references and index
Keywords: Trotter, William Monroe, -- 1872-1934; Guardian (Boston, Mass. : 1901) -- Biography; African American radicals -- United States -- Biography; African American civil rights workers -- Massachusetts -- Boston -- Biography; African American journalists -- Massachusetts -- Boston -- Biography; Journalists -- Massachusetts -- Boston -- Biography; African Americans -- Politcs and government -- 1877-1964; African Americans -- History -- 1877-1964; United States -- Race relations -- History -- 19th century; United States -- Race relations -- History -- 20th century; Biography; History; Biographies